2021
DOI: 10.1007/s10668-021-01434-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term impacts of air pollutants in three megacities of India during COVID-19 lockdown

Abstract: Lockdown was imposed by the Indian government in the month of March 2020 as an early precaution to the COVID-19 pandemic which obstructed the socio-economic growth globally. The main aim of this study was to analyse the impact of lockdown (imposed in March and continued in April 2020) on the existing air quality in three megacities of India (Delhi, Mumbai and Kolkata) by assessing the trends of PM 10 and NO 2 concentrations. A comparison of the percentage reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 76 publications
(116 reference statements)
0
12
0
1
Order By: Relevance
“…Nevertheless, not all evidenced an increase of the pollutants after the lockdown, because of the slow economic recovery [ 48 , 61 , 70 ]. Similarly, studies that compared to the same period in previous years [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ], and even more robustly with historical data of more than 5 years ( Table 1 ), reported a decrease of pollutants’ concentrations during the lockdown. As shown in Table 1 , decreases between 9–60%, 21.4–61.6%, and 30–66% were obtained for PM 2 .…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, not all evidenced an increase of the pollutants after the lockdown, because of the slow economic recovery [ 48 , 61 , 70 ]. Similarly, studies that compared to the same period in previous years [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ], and even more robustly with historical data of more than 5 years ( Table 1 ), reported a decrease of pollutants’ concentrations during the lockdown. As shown in Table 1 , decreases between 9–60%, 21.4–61.6%, and 30–66% were obtained for PM 2 .…”
Section: Discussionmentioning
confidence: 60%
“…A recent study has been done to analyze the spatiotemporal variation of PM 10 and NO 2 over three megacities of India (Delhi, Mumbai and Kolkata). It has been observed that a significant reduction of pollutants has been registered over the megacities during lockdown period and the concentration level of PM 10 has significantly dropped over Kolkata metropolitan area mainly due to imposed of lockdown ( Ganguly et al., 2021 ). But the study has some limitations because the whole study has been conducted within a short time frame and in India, the air pollution parameters are not routinely updated or monitored.…”
Section: Introductionmentioning
confidence: 99%
“…(Tobías et al, 2020) reported a 51% decrease in NO 2 in Barcelona and Spain during the two-week lockdown. Several other studies (Table 1) have indicated a reduction in NO 2 and other pollutants across Indian cities (Biswal et al, 2020;Biswas & Ayantika, 2021;Dumka et al, 2021;Ganguly et al, 2021;Jain & Sharma, 2020;Kumar et al, 2020b;Mahato et al, 2020;Navinya et al, 2020;Selvam et al, 2020;Sharma et al, 2020;Singh et al, 2020a, b) and other cities around the world as an effect of partial and complete lockdown (Acharya & Sreekesh, 2013). Studies indicated that ambient concentrations of pollutants were significantly curtailed as an after effect of the pandemic-related lockdown compared to before lockdown scenarios and last year status.…”
Section: Introductionmentioning
confidence: 95%